Seasonal changes of roosting and foraging areas for Lesser White-fronted Geese Anser erythropus wintering in Japan - Sawa, Yusuke; Hall, Colette; Tamura, Chieko; Nakamura, Noboru (Wildfowl, 2021)
Despite the recent decline in the Eastern Palearctic population of the Lesser White-fronted Goose Anser erythropus (LWfG), numbers wintering in Japan have increased modestly since the 2000s. There have, however, been no systematic studies of the wintering ecology of the species previously conducted in Japan. In this study, count surveys were made of roosting and foraging sites, directed by tracking data from a GPS-tagged bird, to describe the movements of a wintering flock. The home range of the tagged LWfG during the 2020/21 winter was 9,120 ha (core area: 2,080 ha), and the distance between roosting and foraging sites ranged from 1.95–3.64 km. A change in the foraging and roost sites used by the geese was associated with low temperatures in mid-winter. This study provides preliminary information on the movements and habitat use by LWfGs in Japan, but further studies are required to improve our understanding of their wintering ecology, including their feeding habits and energy budgets, in relation to the quality and quantity of food resources available.